Alterations in circadian/seasonal rhythms and vegetative functions are related to suicidality in DSM-5 PTSD - Dell’Osso, Liliana (BMC Psychiatry, 2014)
BACKGROUND: Alterations in rhythmicity and vegetative functions have been reported as correlates of suicidality, particularly in patients with mood disorders. No investigation has addressed their impact on patients with post-traumatic stress disorder (PTSD). Aim of the present study was to fulfill this gap. METHODS: Sixty-five out- and inpatients with DSM-5 PTSD were assessed by using the Mood Spectrum-Self Report-Lifetime Version (MOODS-SR), a questionnaire for lifetime mood spectrum symptomatology including alterations in circadian/seasonal rhythms and vegetative functions. Six items of the MOODS-SR were combined and dichotomized to assess suicidal ideation and/or attempts. RESULTS: Significant and positive associations were found between symptoms of lifetime dysregulations in rhythmicity and vegetative functions and suicidal ideation and/or attempts. All MOODS-SR sub-domains (rhythmicity, sleep, appetite/weight, sexual function, physical symptoms) were associated with an increased likelihood of suicidal ideation, but only changes in appetite/weight were associated with greater odd ratios of suicide attempts (OR = 2.099, 95% CI 1.148-3.841). CONCLUSIONS: Our results suggest that lifetime dysregulations in rhythmicity and vegetative functions may represent correlates of suicidality in patients with DSM-5 PTSD.